Motivating learning - Torralba, Constantino M. (Education quarterly.)
The task of motivating learning will not be a problem if teachers believe that while it is not an easy task, it can and must be done; for motivating learning is of no mean importance. Successful and effective learning relies heavily on the learner's motivation to learn and achieve stated objectives.